THE CORRELATION BETWEEN LAND AND SUBSOIL USE WHEN USING UNDERGROUND SPACE - Kharytonova, T.; Nosik, V.; Kostruba, A.; Mikhailov, V.; Kurilo, M. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
There is a strong bonding of categories when we are to consider problems connected with land. The constant development of social relations brings the necessity to notice what is vital for the legislation to follow those changes. In that order, there is unambiguity in resolving land disputes, particularly about subsoil use. The spatial use of land rights raises a question of clear legislative criteria for their application. For us, it refers to the consideration of the "upper" and "lower" limits of rights distribution. Accordingly, this article investigates the rules of legislation for land and subsoil use. The object of the study is legal problems arising from social relations regarding land and subsoil use. As for the methodology, the following methods were used: analysis, synthesis, deduction, induction, abstraction, generalization, historical and legal methods, formal-legal (dogmatic) method, comparative-legal and sociological-legal methods, legal modeling, and critical-legal method. It has been concluded that domestic legal doctrine includes two approaches to the distribution of owner's rights for the underground space. Additionally, there is a problem of legal demarcation between land and subsoil use. As a result of the study, we offer some ways to solve this issue.
Keywords: subsoil; subsoil code; land use; property rights; urban planning